Wakes and free surface signatures of a generic submarine in the homogeneous and linearly stratified fluid. (15th April 2022) - Huang, Fenglai; Meng, Qingjie; Cao, Liushuai; Wan, Decheng
Abstract: In this paper, a generic submarine Joubert BB2 model travels both in the homogenous and linearly stratified fluid are simulated and investigated. The stable stratification of background density is achieved by specifying the linearly distributed temperature based on a thermocline model. Four main aspects are chosen to discuss the specialty of stratified fluid characteristics by comparing the drag force, downstream wakes, internal waves, and free surface signatures with those of the homogeneous condition. The results show that due to the density gradient and internal waves generation and propagation in the stratified flow, the resistance of the submarine increases. Because of the vertical confinement induced by buoyancy in the stratified environment, the velocity decays faster, thus leading to a broader spread range of wakes in the horizontal plane than the vertical plane. Furthermore, internal waves and anisotropic turbulence stimulated by the moving submarine result in specific signatures on the water surface. A noteworthy anisotropy of the surface wave crest and trough, and a larger influencing zone of the Kelvin waves are shown for the stratified case. Highlights: Proposed a thermocline model to achieve linear density and temperature stratification in STAR-CCM+. Examined the effect of buoyancy when stratified flow past a submarine model with a relatively high Reynolds number. Evaluated the effect of internal waves on the free surface characteristics.